Effects of structural and textural properties of brittle cereal foams on mechanisms of oral breakdown and in vitro starch digestibility. (June 2017) - Alam, Syed Ariful; Pentikäinen, Saara; Närväinen, Johanna; Holopainen-Mantila, Ulla; Poutanen, Kaisa; Sozer, Nesli
Abstract: Structural and textural properties as well as the dietary fibre content of solid cereal foams influence the oral breakdown of structure, bolus formation and digestibility. The aim of this study was to investigate how structural differences of solid cereal foams (puffs vs. flakes) affect in vivo chewing and in vitro starch digestion. Four extruded puffs and flakes were produced from endosperm rye flour by extrusion processing without or with 10% rye bran (RB) addition. Extruded puffs and flakes were masticated by fifteen healthy females and the process was monitored using electromyography. Extruded puffs were more porous than flakes (97% vs 35%). The two products were also significantly different ( p  < 0.05) in their structural and textural properties such as expansion, hardness, density and crispiness. A negative correlation was observed between hardness and crispiness index ( p  < 0.05, r  = − 0.950) and density and porosity ( p  < 0.05, r  = − 0.964). Addition of 10% RB had a significant effect on structural, textural and mastication properties both for puffs and flakes. Mastication of puffs required less total work than flakes (204 vs. 456%) and they were degraded to smaller particles than flakes during mastication. Irrespectively of the considerable differences in structure, texture and oral disintegration process, no significant ( p  < 0.05) differences were observed between puffs and flakes (86.4 vs. 85.1) in terms of starch hydrolysis index. RB addition increased the hydrolysis index of puffs and flakes to 89.7 and 94.5, respectively, which was probably attributable to the increased number of particles in the bolus. Highlights: Extruded puffs were more porous, less hard and crispy compared to flakes. Bran addition had adverse effect on the structural and textural properties of puffs and flakes. Puffs required less mastication work and degraded to smaller particles than flakes. In vitro starch hydrolysis (HI) of puffs & flakes was similar. Rye bran addition increased HI due to increased number of particles in the bolus.